Oil prices and the dynamics of output and real exchange rate - David Meenagh; Patrick Minford; Olayinka Oyekola (Cardiff University, Cardiff Business School, 2015)
We examine the role of oil price shocks in effecting changes both at the aggregate and sectoral levels using an estimated dynamic stochastic equilibrium open economy model. Our main finding is that energy price shocks are not able directly to generate the magnitude of the economic downturn observed in the data. These shocks, however, do possess a strong indirect transmission link that endogenously spreads their effect through the system such that they account for a considerable portion of the U.S. business cycle movements. This leads us to conclude that previous results that attribute a minimal importance to oil price shocks must be focusing more on the energy cost share of gross domestic product and less on how they affect the intertemporal decisions of economic agents. We also find that external shocks have been responsible for explaining volatility in U.S. economic activities for a long time. This leads us to conclude that modelling the U.S. as a closed economy discounts a sizeable set of very relevant factors.
Keywords: E32; D58; F41; C52; Q43; 330; Two sector; non-stationary DSGE model; Oil price; Relative prices; Domestic shocks; Imported shocks